Study of the changes of some physical & chemical parameters accompanied to Ovine and Caprine urinary system infections: Wahab A. Hassan , Khalid M. Hamadi And Zaid S. Hussein - Hassan, Wahab A. (The Iraqi Journal of Veterinary Medicine, 2008)
This study was devoted to determination of normal physical andchemical values of 100 sample of Ovine and Caprine urine withmicroscopically examination of urine samples sterilely collectedfrom sheep & goat slaughtered in Al-Shulla governmental slaughterhouse between may and November 2004 as well as demonstration ofchanges in these values in case of presence of microbes in urine .Thisstudy illustrated no significant differences(P<0.05) of urine analysisvalues between sheep & goat but these values significantlychanged(P<0.05)with the presence of microbes in urine and thesechanges included opacity of urine, decrease of specific gravity &increase of urine pH.25 sample were positive to protein test with concentration extent from 200to 1000mg/dl , 11 samples (44%) were positive to penzedin test. Thebacterial culture of the urine sample showed different species of bacteria thetotal presence of bacteria was 25% in both sheep & goat includingStaphylococcus aurous, Streptococcus spp, Corynobacterium renale,Escherichia coli, Protes vulgaris and Klebsiella pneumonia .